Analisis Peningkatan Produksi Jahe Instan pada IKM Papua Muda Kreatif di Kota Jayapura - Boari, Yoseb; Paula, Diana Yulia; Lestari, Endah Dwi; Patty, Maria Apriyane (Multidisciplinary Journal of Education , Economic and Culture, 2023)
IKM Papua Muda Kreatif is a small company that focuses on the production of instant ginger. They carry out the instant ginger production process starting from the selection of raw ginger to packaging and distribution. The business income of IKM Papua Muda Kreatif fluctuates due to external factors, such as changes in market demand, special events or events, and other factors that affect sales of instant ginger. This study aims to describe the production of instant ginger at IKM Papua Muda Creative, to find out the efforts to increase instant ginger production at IKM Papua Muda Creative and to find out the constraints faced by IKM Papua Muda Creative in running their business. The research method used is direct observation, interviews with owners and workers of IKM, as well as analysis of IKM income data over a certain period. The results of the study show that the description of instant ginger production at IKM Papua Muda Kreatif is carried out through several steps; Selection of raw ginger, cleaning and peeling, slicing or chopping, drying, grinding, packaging, and storage and distribution. Efforts to increase instant ginger production are carried out through looking for references, choosing good raw materials, maintaining a stable fire, looking for interested workers, and attending training. Meanwhile, the obstacles faced by Creative Papuan IKM in running their business are Finance, Marketing and Lack of Human Resources (HR).